The Framing of Dementia in Scientific Articles Published in ‘Alzheimer’s and Dementia’ in 2016 - Oleksandr, Kapranov (Lesya Ukrainka Eastern European National University, 2016)
The present article involves a qualitative study of the framing of dementia in ‘Alzheimer’s and Dementia’, the Journal of the Alzheimer’s Association, published in 2016. The aim of this study is to elucidate how dementia is framed qualitatively in the corpus consisting of scientific articles involving dementia published in ‘Alzheimer’s and Dementia’. The results of the qualitative analysis indicate that dementia is represented in ‘Alzheimer’s and Dementia’ in 2016 as the frames associated with gender, age, costs, caregiver and care-recipients, disability and death, health policy, spatial orientation, medical condition, and ethnic groups. These findings are further discussed in the article. Ця стаття містить фреймовий аналіз концептуалізації деменції в дискурсі наукової літератури, опублікованої в журналі «Alzheimer’s and Dementia» у 2016. Метa фреймового аналізу полягає у виявленні концептуалізації деменції в часописі «Alzheimer’s and Dementia». Результати фреймового аналізу показують, що деменція в «Alzheimer’s and Dementia» розглядається в межах таких категорій: стать, вік, кошти, догляд, інвалідність та смертність, політика в галузі охорони здоров’я, просторова орієнтація, стан здоров’я та етнічні групи. Ці результати обговорюються далі в статті.
Keywords: dementia; discourse; framing; psycholinguistics; деменція; дискурс; психолінгвістика; фрейм